Immigrant entrepreneurship in Romania: Drawing best practices from Middle Eastern immigrant entrepreneurs' experiences - Ozgur Ozmen; Raluca Mariana Grosu; Mariana Dragusin (Amfiteatru Economic Journal, 2021)
Migrant entrepreneurship represents a topic of a high societal and academic significance. For a host country, immigrant entrepreneurs' endeavours are, in many cases, an under-utilized lever for local and regional economic revival. Based on a complex field research carried out between July 2017 and December 2018, the present paper approaches immigrant entrepreneurship in Romania, with a particular focus on Middle Eastern immigrant entrepreneurs. Our multi-method qualitative field research - consisting of semi-structured interviews, observations and informal discussions - envisaged 97 immigrant businesses, targeting the analysis of the phenomenon from different perspectives: economic, social, cultural, political, and institutional. Aiming to draw best practices from the investigated Middle Eastern immigrant entrepreneurs' experiences, the research results outlined in this paper emphasize both descriptive and practical features. Migration-related particularities, entrepreneurs' profile, business obstacles, business practices, or perspectives on and comparisons of the Romanian business environment with the one in the origin country represent just few examples of aspects thoroughly approached in the paper.
Keywords: F22; J15; M10; M20; O15; 330; migration; entrepreneurship; immigrant entrepreneurship; immigrant entrepreneur; Romania; Middle Eastern immigrants